Walking Together: Towards a Collaborative Model for Maternal Health Care in Pastoralist Communities of Laikipia and Samburu, Kenya - Kermode, Michelle; Morgan, Alison; Nyagero, Josephat; Nderitu, Florence; Caulfield, Tanya; Reeve, Matthew; Nduba, John (My University)
Purpose: In 2009 the Kenyan Government introduced health system reforms to address persistently high maternal and newborn mortality including deployment of skilled birth attendants (SBAs) to health facilities in remote areas, and proscription of births attended by traditional birth attendants (TBAs). Despite these initiatives, uptake of SBA services remains low and inequitably distributed. This paper describes the development of an SBA/TBA collaborative model of maternal health care for pastoralist communities in Laikipia and Samburu. Description: A range of approaches were used to generate a comprehensive understanding of the maternal and child health issues affecting these pastoralist communities including community and government consultations, creation of a booklet and film recognising the contributions of both TBAs and SBAs that formed the basis of subsequent discussions, and mixed methods research projects. Based on the knowledge and understanding collectively generated by these approaches we developed an evidence-based, locally acceptable and feasible model for SBA/TBA collaborative care of women during pregnancy and childbirth. Assessment: The proposed collaborative care model includes: antenatal and post-natal care delivered by both SBAs and TBAs; TBAs as birth companions who support women and SBAs; training TBAs in recognition of birth complications, nutrition during and following birth, referral processes, and family planning; training SBAs in respectful maternity care; and affordable, feasible redesign of health facility infrastructure and services so they better meet the identified needs of pastoralist women and their families. Conclusion: The transition from births predominantly attended by TBAs to births attended by SBAs is likely to be a gradual one, and an interim SBA/TBA collaborative model of care 3 has the potential to maximise the safety of pastoralist women and babies during the transition phase, and may even accelerate the transition itself. SIGNIFICANCE Kenya has a high burden of maternal and newborn mortality. Consequently, health system reforms were introduced to promote availability of skilled birth attendants (SBAs) and discourage deliveries by traditional birth attendants (TBAs). Despite these changes, only 10% of women from semi-nomadic pastoralist communities are delivered by an SBA; the majority are delivered by TBAs at home. Using a consultative, multi-method, research focused approach involving communities, SBAs, TBAs and government, we developed a collaborative model of SBA/TBA maternal health care to promote better uptake of health facility births in pastoralist communities.
Accepted version
Keywords: Maternal health; Pastoralist communities; Collaborative models of care; Kenya; Traditional birth attendants; Skilled birth attendants